Differences in pollinator composition, species richness and flower visit abundance between Centaurea jacea (L.) and Leontodon hispidis (L.) in a meadow in Central Slovenia - Maarten De Groot (Natura Sloveniae)
In this pilot study, the differences in pollinator composition, species richness and pollinators’ visits between Centaurea jacea and Leontodon hispidis were investigated. For 15 minutes, the pollinators visiting the plants in a particular meadow were counted. There was a difference in composition. On C. jacea mostly Apis mellifera occurred, while L. hispidis was visited mainly by syrphids. Furthermore, due to the frequent visits by Apis mellifera, the abundance of pollinators on C. jacea was higher then on L. hispidis, while the evenness was higher in L. hispidis. The species richness did not differ between the plant species. The reasons for differences in pollinator visitation are discussed. Furthermore, it would be advisable to survey the differences in pollinator composition and abundance between similar plant species within the tribes/families of C. jacea and L. hispidis, for a better understanding of the pollinators’ choice for a plant species.